2011
DOI: 10.1016/j.ijplas.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-plasticity finite-element analysis of inelastic behavior during unloading in a magnesium alloy sheet

Abstract: a b s t r a c tA crystal-plasticity finite-element analysis of the loading-unloading process under uniaxial tension of a rolled magnesium alloy sheet was carried out, and the mechanism of the inelastic response during unloading was examined, focusing on the effects of basal and nonbasal slip systems. The prismatic and basal slip systems were mainly activated during loading, but the activation of the prismatic slip systems was more dominant. Thus the overall stress level during loading was determined primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 61 publications
7
89
0
Order By: Relevance
“…Hama and Takuda [3] claimed that the activity of the basal slip systems depends on the inhomogeneity of the materials. In addition, homogeneous deformation is possible only when the second-order pyramidal slip systems are active, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Hama and Takuda [3] claimed that the activity of the basal slip systems depends on the inhomogeneity of the materials. In addition, homogeneous deformation is possible only when the second-order pyramidal slip systems are active, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,12) Because the program is on the basis of the rate form of the principle of virtual work, 37) Eqs. (1), (2), and (8) were utilized in their rate forms.…”
Section: Crystal Plasticity Finite-element Methodsmentioning
confidence: 99%
“…1,3) On the other hand, owing to recent advances in numerical technique and computational power, crystal-plasticity models are recently employed also to quantitative prediction of work-hardening behavior such as stress-strain curves and contour of plastic work. So far, the deformation behavior in face-centered cubic (fcc) 7,8) and hexagonal close-packed (hcp) [9][10][11][12] materials is able to be predicted fairly well using crystal-plasticity models. In contrast, the prediction accuracy of deformation in body-centered cubic (bcc) metals is still poor as compared to fcc and hcp metals.…”
Section: Introductionmentioning
confidence: 99%
“…the instantaneous reverse movement of the mobile dislocations. 18,22,24) The authors 24) have examined the effect of the strain rate sensitivity exponent on the stressstrain curve during unloading in a Mg alloy sheet using the crystal plasticity finite-element method. It was found that the initial rapid decrease does not occur when the strain rate sensitivity exponent is set to nearly zero, whereas it is more pronounced as the strain rate sensitivity exponent becomes large.…”
Section: Relationship Between Nonlinearity and Apparent Elastic Modulusmentioning
confidence: 99%
“…We also depicted that the nonlinear deformation during unloading in the Mg alloy sheet can be predicted well using a crystal plasticity finiteelement simulation. 24,25) The aforementioned studies exhibited that the nonlinear deformation during unloading is observed in various metal sheets and the nonlinearity during unloading plays an important role in the springback prediction. Recently the nonlinear effects are being taken into account in the constitutive models.…”
Section: Introductionmentioning
confidence: 99%